2020
DOI: 10.1186/s12875-020-01118-9
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of, attitude toward, and willingness to participate in pay for performance programs among family physicians: a cross-sectional study

Abstract: Background: The National Health Insurance Administration of Taiwan has introduced several pay-for-performance programs to improve the quality of healthcare. This study aimed to provide government with evidence-based research findings to help primary care physicians to actively engage in pay-for-performance programs. Methods: We conducted a questionnaire survey among family physicians with age-stratified sampling from September 2016 to December 2017. The structured questionnaire consisted of items including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…Interviewed physicians saw P4P strategies as a key element for behavior change, yet the uptake in ARena did not match this perception. A recent survey study conducted among family physicians to understand awareness and attitudes towards participation in P4P programs identified major reasons for rejecting additional reimbursements in increased loads of administrative work (79.6%) and inadequate understandings of the P4P content (62.9%) [40]. This cannot be supported by our data, but could explain the heterogenous results.…”
Section: Comparison To Prior Researchcontrasting
confidence: 73%
“…Interviewed physicians saw P4P strategies as a key element for behavior change, yet the uptake in ARena did not match this perception. A recent survey study conducted among family physicians to understand awareness and attitudes towards participation in P4P programs identified major reasons for rejecting additional reimbursements in increased loads of administrative work (79.6%) and inadequate understandings of the P4P content (62.9%) [40]. This cannot be supported by our data, but could explain the heterogenous results.…”
Section: Comparison To Prior Researchcontrasting
confidence: 73%
“…However, additional compensation might only be an incentive to participate in a study, but of lesser importance after this decision is taken [ 41 ]. Jan et al [ 46 ] also identified increased administrative workloads and inadequate understandings of performance-based payment contents as principal reasons for aversions of family practitioners to engage. These aspects are not echoed in this study but can be considered for explanation.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional compensation might only be an incentive to participate in a study, but of lesser importance after this decision is taken [39]. Jan et al [44] also identi ed increased administrative workloads and inadequate understandings of performance-based payment contents as principal reasons for aversions of family practitioners to engage. These aspects are not echoed in this study but can be considered for explanation.…”
Section: Discussionmentioning
confidence: 99%